'Brexit' and International Insolvency Beyond the Realm of Mutual Trust. Issue 3 (8th September 2017) - Carballo Piñeiro, Laura
Abstract: The outcome of the referendum held in the UK in June 2016 is of far‐reaching and unpredictable consequences. This article focuses on the particular field of international insolvency with a view to identifying some of them, all arising out of the fact that the UK will be leaving the EU area of justice and the strong cooperation based on mutual trust between member states. This will make UK–EU insolvency cases clearly less efficient and effective. The consequences of Brexit could be mitigated by the already existing coordination among the international instruments dealing with these matters, in particular the European Insolvency Regulation and the UNCITRAL Model Law on Cross‐Border Insolvency. However, not all EU member states have in place rules dealing with these issues as regards to third states. In order to lessen the impact of Brexit in this sensitive area of law, the implementation of the Model Law in order to deal with extra‐EU cross‐border insolvency could be of avail. Copyright © 2017 INSOL International and John Wiley & Sons, Ltd